Mobile Assisted-Based Learning in Teaching Literature: Raising Students’ Environmental Awareness and Appreciation in EFL Classroom - Wuntu, Ceisy Nita; Ali, Muhammad Ilham; Tatipang, Devilito Prasetyo; Rorintulus, Olga A.; Manuas, Maissy (UNIB Press, 2024)
Teaching literature enhances sensitivity to life's values across diverse cultural expressions, while culturally grounded English aims to instill an appreciation for these values. Environmental themes in literary works underscore safety and sustainability and promote public awareness and appreciation for environmental preservation. The article explores how mobile-assisted learning can enhance students' understanding and appreciation of environmental themes in literature within the context of English as a Foreign Language (EFL) classrooms. This study is qualitative research, using semi-structured interviews and questionnaires as the instruments by which the data were collected. Involving 32 English Education Department students, this study presents information about mobile-assisted learning (MAL) applications in teaching literature. As a result, through the MAL model, students engage in various activities in the classroom, such as reading, writing, discussing, and presenting ideas. Students' enthusiasm indicates their deep understanding of the effectiveness of the MAL learning model for visual attraction and clarity. It provides visual information about the dangerous effects of environmental damage. This could be seen in their responses to sadness, worry, anxiety, and anger. Further research could use this finding as a new starting point to explore specific mobile apps' effectiveness, long-term impacts on literary awareness and appreciation, comparative studies across different age groups, and the role of teacher facilitation in mobile-assisted EFL literature instruction.